Roman and Modern Emphyteusis - Novkirishka-Stoyanova, Malina (Yearbook of the Law Department, 2021)
The study examines a specific form of concession or lease of land associated with obligations to cultivate and ameliorate. It is divided into two parts – for the Roman and for the modern emphyteusis. In Part I they present the theories of the origin of emphyteusis in Roman law, as well as the characteristics of emphyteutic law (ius emphyteuticarium), which appears to be very specific (sui generis, iustertium) and different from the traditionally defined ius in rem and ius in personam. It is the result of the development of the Roman legal concept of public property and its management since the archaic period, it has its design in the so-called duplex dominium during the time of the Republic and the Empire and passed into medieval law in the system of divided ownership (dominium divisum). The concept of emphyteusis as a legal form of dominium utile and directly related to the feudal regime was one of the reasons for its denial in the age of Revolutions, but its dogmatic and functional usefulness necessitated its preservation in a number of civil codifications and agrarian laws even today.